The magnificent seven (2016) [videorecording (DVD)] - Washington, Denzel, 1954-; Pratt, Chris, 1979-; Hawke, Ethan, 1970-; D'Onofrio, Vincent (Sony Pictures Home Entertainment, 2016)
The town of Rose Creek is under the deadly control of Bartholomew Bogue, the townspeople are desperate for protection. They find protection in seven outlaws. These seven mercenaries find themselves fighting for more than money.